KADAR Fe DAN Zn DALAM KRIM KENTAL MANIS KEMASAN KALENG EXPIRE DAN NON EXPIRE MENGGUNAKAN HIDROGEN PEROKSIDA (H2O2) UNTUK DESTRUKSI BASAH SECARA SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Putri Go; I W. Sudiarta; P. Suarya (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2019)
Sweetened condensed milk is generally packaged in a can which is made from iron and zinc. Iron and zinc can have corrosion with the increasing of contact time and changing condition so that they will contaminate the milk. The purpose of this research are to determine the best wet destruction method, find out the effect of adding 30% H2O2 at varied volume in the process of wet destruction, to find out Fe and Zn content in expire and non-expired sweetened condensed milk and to compare the results with the national quality standard. Sample was wet destructed by using variation of 70% HNO3: 30% H2O2 which is 3:0 (method A); 3:0.5 (method B) 3:1 (method C); 3:2 (method D) then the results were measured by using Atomic Absorption Spectrophotometer. Analysis of Fe used standard addition curve method whereas the analysis of Zn used calibration curve method. The results of the analysis showed that the best variation of HNO3:H2O2 in wet destruction method was 3:0.5 for Fe analysis and 3:2 for Zn analysis. The addition of 30% H2O2 at varied volume in wet destruction for Fe analysis gave significantly different results for non-expired sweetened condensed milk but were not significantly different for expired sweetened condensed milk. Whereas, the analysis of Zn gave significantly different results for both non-expired and expired sweetened condensed milk. The metal content in the expired and non-expired sweetened condensed milk which were wet destructed by using the best solvent compotition obtained 0,2759 and 0,7126 mg/kg for Fe and 4,1645 and 2,4367 mg/kg for Zn metal. The Fe and Zn content in the sweetened condensed milk are still below the maximum limit that set by SNI. Keywords: Fe, H2O2, Atomic Absorption Spectrophotometer, sweetened condensed milk, Zn